UNCERTAINTY IN STATIC PRESSURE CORRECTION IN A SUBSONIC WIND TUNNEL - Reis, M. L. C. C.; Mello, O. A. F.; Chisaki, M. (Revista de Engenharia Térmica, 2004)
The static pressure p on the subsonic Wind Tunnel of the Aerodynamic Testing Laboratory of the Institute of Aeronautics and Space IAE, Aerospace Technical Center CTA, is measured using an absolute pressure sensor, located on the upper test section wall. This measurement is not taken at the same location as the one where the model is mounted during the actual wind tunnel test. This fact raises the need for a correction during data reduction. The identification and evaluation of the associated error source is important because the static pressure is an input quantity for the calculation of the total pressure pt, Mach number M and density ρ during the test. The present paper is concerned with the determination of the relationship between the static pressure measured on the tunnels upper wall and that at the model location, and with the analysis of the uncertainty propagation for the measured flow parameters.